Kdo in zakaj potrebuje Program nagrajevanja za varnostne hrošče? - Tomašević, Denis (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
In Slovenia, vulnerability scanning is already quite well established with security scans conducted once a year (a campaign approach prescribed by regulators). These scans are expensive due to their scope and the limited number of experts in Slovenia, but they cost the same regardless of whether a solution has a thousand vulnerabilities or none. The Security Bug Bounty program provides coverage 365 days a year and an unlimited pool of experts from all over the world for a price that is proportional to the current security condition of the solution. The content of the article will be useful both for those who would like to start searching for security vulnerabilities (as a main or additional source of income), for those who create vulnerabilities (developers, architects, solution managers, etc.), and for those who should take care of the secure operation of solutions (development managers and experts in information security and compliance with regulatory frameworks).